2021
DOI: 10.3389/fgene.2021.617512
|View full text |Cite
|
Sign up to set email alerts
|

An Information Theoretical Multilayer Network Approach to Breast Cancer Transcriptional Regulation

Abstract: Breast cancer is a complex, highly heterogeneous disease at multiple levels ranging from its genetic origins and molecular processes to clinical manifestations. This heterogeneity has given rise to the so-called intrinsic or molecular breast cancer subtypes. Aside from classification, these subtypes have set a basis for differential prognosis and treatment. Multiple regulatory mechanisms—involving a variety of biomolecular entities—suffer from alterations leading to the diseased phenotypes. Information theoret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 60 publications
0
3
0
Order By: Relevance
“…Further steps towards the understanding of co-expression patterns and the differences in clustering among adjacent normal and cancerous phenotypes may be also based on the usage of multi-layer approaches ( 11 , 70 ).…”
Section: Discussionmentioning
confidence: 99%
“…Further steps towards the understanding of co-expression patterns and the differences in clustering among adjacent normal and cancerous phenotypes may be also based on the usage of multi-layer approaches ( 11 , 70 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, for the purpose of network reconstruction, issues such as batch effects and sample sizes may introduce additional confounding factors. An alternative approach is the use of cross-validation strategies, such as the ones used for recent multiomic network reconstructions [ 63 ]. Such approaches have shown that these methods lead to robust link prediction results.…”
Section: Discussionmentioning
confidence: 99%
“…Pre-processing has been described before ( Ochoa et al, 2021 ) and follows published guidelines ( Aryee et al, 2014 ; Tam et al, 2015 ; Tarazona et al, 2015 ). As a first step, only protein-coding transcripts were kept since for our purposes, these were considered the main functional effectors.…”
Section: Methodsmentioning
confidence: 99%